2021
DOI: 10.1109/tcst.2020.2977302
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Control of an Articulated Intervention Autonomous Underwater Vehicle in 6DOF Using Generalized Super-twisting: Theory and Experiments

Abstract: The articulated intervention autonomous underwater vehicle (AIAUV) is an underwater swimming manipulator with intervention capabilities. Station-keeping and trajectory tracking are essential for the AIAUV to be able to move in confined spaces and to perform intervention tasks. In this paper, we propose using a generalized super-twisting algorithm (GSTA), which is an extension of the regular super-twisting algorithm, for the trajectory tracking of the position and orientation of the base of the AIAUV in 6DOF. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The error between u eq and its approximation Ć«eq can be very small via selecting an appropriate time constant 𝜏. 22,51 Assumption 3 (52,53). For lumped disturbance đš« a , there exists â€–đš« a ‖ ≀ 𝛿 a â€–đšœ 1 (S)‖, where 𝛿 a is an unknown positive constant.…”
Section: Ism-based Amgst Control For Attitude Subsystemmentioning
confidence: 99%
“…The error between u eq and its approximation Ć«eq can be very small via selecting an appropriate time constant 𝜏. 22,51 Assumption 3 (52,53). For lumped disturbance đš« a , there exists â€–đš« a ‖ ≀ 𝛿 a â€–đšœ 1 (S)‖, where 𝛿 a is an unknown positive constant.…”
Section: Ism-based Amgst Control For Attitude Subsystemmentioning
confidence: 99%
“…Although first-order sliding-mode control (SMC) laws are well known to ensure the stability of the equilibrium points of many systems subjected to disturbances and uncertainties, these techniques require infinite control bandwidths [1]. To resolve this critical problem, a continuous SMC based on a super-twisting algorithm was proposed [2]. In [3], a second-order SMC was developed by redesigning a super-twisting algorithm using saturation functions and backstepping-like techniques.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously investigated the use of SMC for trajectory tracking for an AIAUV, since trajectory tracking is essential to allow an AIAUV to move in confined spaces and to perform intervention tasks (tasks where the robot interacts or is in contact with the environment). In References 21 and 22, we investigated the use of the STA with adaptive gains to control an AIAUV, and in References 23 and 24, we investigated the use of the original GSTA for this purpose. In Reference 25, we compared these two SMC algorithms through both simulations and experiments, and we observed that the STA with adaptive gains yielded better tracking results than the GSTA, even though the GSTA has better theoretical properties as it is proven to provide GFT stability for a larger class of systems.…”
Section: Introductionmentioning
confidence: 99%